Beyond this harbor : adventurous tales of the heart - Styron, Rose (Alfred A. Knopf, 2023)
"A memoir of an extraordinary life--poet, international human rights activist, founding member of Amnesty International USA, journalist, hostess, famous beauty, foreign policy advisor; friend to politicians, movie stars, the legendary; discoverer of Philip Roth, longtime wife of Bill Styron and together, America's literary golden couple at home and abroad"--Amazon.com